Mikrologia codzienności. Rekwizyty w tomie Drobiazgi Marty Reszczyńskiej-Stypińskiej - Gielarek-Gorczyca, Krystyna (Przestrzenie Teorii, 2025)
This article aims to explore the role of props in Marta Reszczyńska-Stypińska’s poetic volume entitled Trinkets in a literary, cultural and philosophical context, using the concepts of micrology and materiality. Looking at these inconspicuous objects can contribute to the creation of new and often non-obvious poetic interpretations. Reszczynska’s work opens up new avenues in the study of the everyday, suggesting that objects can create complex meanings that are often overlooked in conventional sociological and cultural studies. The analysis in this volume fits into the broader context of research on the materiality of culture, with an emphasis on the material turn and micrology, which, as Arjun Appadurai has pointed out, considers objects as active participants in the creation of values and social relations. Future research could focus on comparative analyses with other micrological authors and further explore the influence of materiality on the interpretation of literary narratives.